Penilaian kesehatan visual dan internal pohon besar di Kebun Raya Eka Karya Bali - Indi Swari, Komang Kartika; Ginantra, Ketut; Hanum, Siti Fatimah (Jurnal Biologi Udayana; Vol 26 No 1 (2022): JURNAL BIOLOGI UDAYANA, 2022)
Eka Karya Bali Botanical Gardens has several large and old trees that have signs of damage and risk endangering visitors safety. Trees health assessments are very important to prevent the risk of fallen trees. This study aims to determine the trees health and the relationship between internal and visual damage to trees in the Eka Karya Bali Botanical Garden. The criteria for the sample tree is that the tree has a circumference of more than 250 cm, and grows in a location with a lot of visitor activity. The research was carried out from February 2021-January 2022 at the Eka Karya Bali Botanical Garden. Visual assessment of trees used a modified Tree Risk Assessment Form, while internal assessment used   Arborsonic 3D Acoustic Tomograph. Visual and internal results were scored, then Pearson correlation was tested on visual and internal results. The visual assessment results found 19% of high risk trees, 73% of medium risk trees, and 8% of low risk trees while the internal assessment found 65% low risk trees, 27% medium risk trees, and 8% high risk trees. The tree with a high risk for both results is  Prunus cerasoides on plot XIII.B No. 17 and plot XII.A No. 3. Furthermore, internal and visual damage to trees have a strong positive relationship with a correlation value is 0.691.